Correlation between orphan nuclear receptor Nurr1 expression and amyloid deposition in 5XFAD mice, an animal model of Alzheimer's disease. (16th September 2014) - Moon, Minho; Jeong, Inhye; Kim, Chun‐Hyung; Kim, Jihong; Lee, Paula K. J.; Mook‐Jung, Inhee; Leblanc, Pierre; Kim, Kwang‐Soo
Abstract The functional roles of the orphan nuclear receptor, Nurr1, have been extensively studied and well established in the development and survival of midbrain dopamine neurons. As Nurr1 and other NR4A members are widely expressed in the brain in overlapping and distinct manners, it has been an open question whether Nurr1 has important function(s) in other brain areas. Recent studies suggest that up‐regulation of Nurr1 expression is critical for cognitive functions and/or long‐term memory in forebrain areas including hippocampal formation. Questions remain about the association between Nurr1 expression and Alzheimer's disease (AD) brain pathology. Here, using our newly developed Nurr1‐selective antibody, we report that Nurr1 protein is prominently expressed in brain areas with Aβ accumulation, that is, the subiculum and the frontal cortex, in the 5XFAD mouse and that Nurr1 is highly co‐expressed with Aβ at early stages. Furthermore, the number of Nurr1‐expressing cells significantly declines in the 5XFAD mouse in an age‐dependent manner, accompanied by increased plaque deposition. Thus, our findings suggest that altered expression of Nurr1 is associated with AD progression. <boxed-text content-type="graphic" id="jnc12935-blkfxd-0100" position="anchor" orientation="portrait"> </boxed-text> Using our newly developed Nurr1‐selective antibody, we show that Nurr1 protein is prominently expressed in brain areas accumulating amyloid‐beta (Aβ) in the transgenic mouse model of Alzheimer's disease (AD) and that Nurr1 is highly co‐expressed with Aβ at early stages (upper panel). Furthermore, in the AD brain the number of Nurr1‐expressing cells significantly declines in an age‐dependent manner concomitant with increased Aβ accumulation (lower diagram) highlighting a possible Nurr1 involvement in AD pathology.